Electroencephalography in congenital malformations of the central nervous system - Patrícia Campos; Guillermo Cruz; Rodolfo Lizarraga; Ernesto Bancalari; Daniel Guillen; Carlos Castañeda (Arquivos de Neuro-Psiquiatria)
We studied clinical and EEG features of 36 cases with congenital malformations of the CNS. Patients were followed at the outpatient clinic of Hospital Cayetano Heredia and of Hogar Clinica San Juan de Dios in Lima-Peru, from January 1984 to June 1992. Eighty percent of the patients had convulsive syndromes and mental retardation. The most frequent malformation was agenesis of corpus callosum, and it was not possible to find a "typical" EEG pattern. The second were porencephalic cysts, with a good clinical-EEG correlation. There were two typical cases of schizencephaly, one of hemimegalencephaly with good prognosis, and one of holoprosencephaly. The results are compared to those obtained for a series we previously reported. Data discussed take into account reports on the subject registered in the literature. It is concluded that EEG is an useful method to evaluate possible CNS malformations in developing countries.